2017
DOI: 10.21037/jtd.2017.03.99
|View full text |Cite
|
Sign up to set email alerts
|

Cannulation strategies for aortic surgery: which is the best one?

Abstract: The choice of the optimal arterial cannulation strategy for surgery on proximal aorta and arch remains a controversial area and a subject of intense debate. The search for the best cannulation strategy for aortic surgery assumes increasing importance due to its impact on clinical outcomes. Several cannulation strategies have been proposed to establish cardiopulmonary bypass (CPB) for aortic surgery and each one of these has its pros and cons. These cannulation strategies can be broadly classified into central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Nevertheless, most surgeons prefer central cannulation which is AA, innominate and axillary artery cannulation rather than peripheral cannulation such as femoral artery cannulation. There has been increasing the use of axillary artery cannulation due to its safety and technical feasibility, especially in patients with diseased AA or femoral artery . Raja et al reported that femoral artery cannulation is usually reserved for challenging cases such as aortic dissection or chronic proximal aortic and arch aneurysms.…”
Section: Cannulation In Emergency Settingsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, most surgeons prefer central cannulation which is AA, innominate and axillary artery cannulation rather than peripheral cannulation such as femoral artery cannulation. There has been increasing the use of axillary artery cannulation due to its safety and technical feasibility, especially in patients with diseased AA or femoral artery . Raja et al reported that femoral artery cannulation is usually reserved for challenging cases such as aortic dissection or chronic proximal aortic and arch aneurysms.…”
Section: Cannulation In Emergency Settingsmentioning
confidence: 99%
“…There has been increasing the use of axillary artery cannulation due to its safety and technical feasibility, especially in patients with diseased AA or femoral artery . Raja et al reported that femoral artery cannulation is usually reserved for challenging cases such as aortic dissection or chronic proximal aortic and arch aneurysms. However, the risk of retrograde cerebral embolization, organ malperfusion, perfusion of the false lumen, and retrograde dissection due to flow reversal in the thoracoabdominal aorta, can be increased by femoral cannulation .…”
Section: Cannulation In Emergency Settingsmentioning
confidence: 99%
See 3 more Smart Citations